Vectors for Increasing the Effectiveness of Profit Management at Company Level - FurmanІ.V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Imperfect management of processes involved in accumulation and disposal of profit at Ukrainian companies affects their performance, with the consequent losses of public budget revenues. This raises the need for new and more effective mechanisms for accumulation and disposal of corporate profit, which would be focused on maximal utilization of production, marketing and fiscal capacities of business entities and enhancement of their competitiveness at domestic and global market. The article’s objective is to conduct theoretical study of profit as an economic category and an essential component of company’s performance, sum up the principles of profit management, and analyze the profit management system at company level. A brief review of theoretical definitions of profit is made, economic origin of profit and its role in business operation in the Ukrainian context is highlighted. The components of profit management system at company level, essential principles of strategic management of company profit, organizational and economic mechanism for company profit management, a strategy for profit management at company level is discussed and summed up. The organizational and economic mechanism for profit quality management at company level is proposed.